Information and Communication Technology (ICT) and Insurance Companies Profitability in Nigeria - Olajide Solomon Fadun (STIE Malangkucecwara, 2013)
The study examines the impact of Information and Communication Technology (ICT) on insurance companies' profitability. It identifies the imperatives for adoption of ICT to promoting efficient and efficient service delivery in the insurance industry as a strategy for attainment of the profit maximization objectives of insurance companies in Nigeria. It is an empirical design study, using responses of structured questionnaire of 152 respondents from 18 insurance companies. The study concludes that there is a positive relationship between ICT adoption and insurance companies' profitability in Nigeria. This implies that adoption of ICT by insurance companies can enhance their efficiency, their quality of service delivery, and their profitability. The implication of the findings for practice is that insurance companies should endeavour to update their ITC facilities regularly, in view of its impacts on quality of service delivery and profitability. The paper highlights the need for regular training of insurance personnel to keep them abreast of the current innovations in the use of ICT so as to ensure that the industry contribute positively to the economy.